A mathematical model for predicting oil-water separation efficiency in a de-oiling hydrocyclone. Issue 9 (2nd September 2017) - Huang, Qian; Li, Changjun; Li, Ping
ABSTRACT: The de-oiling hydrocyclone is among the most effective devices to recover oil from oily wastewater. In this work, a new model is theoretically developed to predict the separation efficiency of oil droplets in hydrocyclones. According to the analysis of the flow pattern, the droplet dynamics, and oil concentration distribution in the de-oiling hydrocyclone, the differential equation for the new model is established based on the principle of the mass balance of oil droplet. The proposed model can be finally expressed as a simple explicit function including the main geometrical dimensions and operating parameters. The availability of this model is validated by comparison of the calculated grade efficiency with experimental data and other theoretical separation model. GRAPHICAL ABSTRACT: